The Relationship between Peer Conformity and Students' Phubbing Behavior Tendency - Adinda Amalia; Rahmi Dwi Febriani; Dina Sukma; Rezki Hariko (Universitas PGRI SUMATERA BARAT, 2025)
Phubbing behavior is a phenomenon where individuals ignore their conversation partners in direct interactions because they are too focused on their smartphones. This phubbing behavior is increasingly prevalent and has become a serious concern considering its impact on the quality of social interactions and interpersonal development. The influence of smartphone use makes students careless and insensitive to their surroundings. One factor suspected of contributing to the level of phubbing behavior tendencies is peer conformity. Therefore, this study aims to describe and analyze the relationship between peer conformity and students' phubbing behavior tendencies. This study used a quantitative method with a descriptive correlational research type. The research sample was 208 students using a simple random sampling technique. The instruments used were a peer conformity scale with a reliability level of 0.945 and a student phubbing behavior tendency scale with a reliability level of 0.881. Data were analyzed using Spearman correlation with the JASP 0.19.3.0 program for Windows. The findings of this study indicate that the relationship between peer conformity and students' tendency to phubbing behavior is generally in the moderate category with a Spearman correlation coefficient value of 0.400 (ρ < 0.001). The positive correlation results indicate that the higher the peer conformity, the higher the tendency of students to phubbing behavior. This study recommends the need for comprehensive efforts by school counselors and related parties to develop counseling service plans to reduce the tendency of phubbing behavior. Keywords: Peer conformity, phubbing behavior, smartphone, students, counseling